E-COMMERCE BIBIT IKAN BERBASIS ANDROID SEBAGAI KATALISATOR PENINGKATAN PENJUALAN HASIL TERNAK IKAN DI KABUPATAN PRINGSEWU - Rasid , Muhammad; Junaidi, Muhammad; Sodikin (JURNAL LIMITS, 2023)
E-commerce is the impact of developments in information and telecommunications technology, thereby significantly changing the way humans interact with their environment, which in this case is related to trade mechanisms. So far, Lampung has been known as a center for the production of marine fish farming (mariculture), especially grouper, shrimp and freshwater fish. One of the well-known freshwater fish production centers in Lampung Province is in Pagelaran District, Pringsewu Regency. And with the development of current information technology, the authors designed an e-business system for selling fish fingerlings based on Android to help sellers market fish seeds and make it easier for customers, suppliers and business partners to carry out transactions, buying and selling and as promotional media. In this research the method of collecting data was interview, observation, and literature study, then the methodology used was the Android-based Development Life Cycle (SDLC) System.